A marine biofilm flow cell for in situ screening marine fouling control coatings using optical coherence tomography. (15th December 2018) - Fabbri, Stefania; Dennington, Simon P.; Price, Clayton; Stoodley, Paul; Longyear, Jennifer
Abstract: A novel fouling marine flow cell was designed and fitted with a clear plastic lid to allow real-time imaging of biofilms using optical coherence tomography (OCT). Marine biofilms were grown under controlled shear flow on coupons coated with 6 different biocidal antifouling coatings (SPC1, SPC2, SPC3, SPC4, CDP1 and CDP2, AkzoNobel) and one inert coating which contained no biocidal actives (NB-D) for 8 weeks. One set of coupons coated with NB was statically immersed in sea water during the same time period (NB-S). Biofilm removal was assessed by increasing the flow velocity while OCT simultaneously measured the biofilm cross-sectional area (CSA). The highest initial removal rates were observed for NB-S, NB-D, and SPC2. Percent biofilm cross-sectional area reduction (%CSAred) was higher on SPCs (>60%) compared to CDPs (<50%). SPCs had the highest percent reduction in biofilm surface area coverage (%SACred >60%) compared to the CDPs (<20%). The marine biofilm flow cell combined with OCT can be used to screen for coating-specific differences in biofilm growth and removal in real time rather than traditional before and after surface area coverage measurements. Future testing will focus on how the biofilm-coatings interactions interact with biofilm mechanical and structural properties to produce drag.